2021
DOI: 10.24272/j.issn.2095-8137.2020.354
|View full text |Cite
|
Sign up to set email alerts
|

Cataract-causing allele in CRYAA (Y118D) proceeds through endoplasmic reticulum stress in mouse model

Abstract: As small heat shock proteins, α-crystallins function as molecular chaperones and inhibit the misfolding and aggregation of β/γ-crystallins. Genetic mutations of CRYAA are associated with protein aggregation and cataract occurrence. One possible process underlying cataract formation is that endoplasmic reticulum stress (ERS) induces the unfolded protein response (UPR), leading to apoptosis. However, the pathogenic mechanism related to this remains unexplored. Here, we successfully constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Gene variants in CRYAA can potentially lead to endoplasmic reticulum stress (ERS)-induced unfolded protein response (UPR) during lens development, causing cellular apoptosis and subsequently leading to cataract formation. [35] Variants in the CRYBA1 gene may lead to abnormalities in protein structure, preventing proper folding and assembly and thereby impacting the normal development and transparency of the lens. In addition to hereditary cataracts, CRYBA1 variants may also be associated with other ocular abnormalities such as corneal lesions and retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Gene variants in CRYAA can potentially lead to endoplasmic reticulum stress (ERS)-induced unfolded protein response (UPR) during lens development, causing cellular apoptosis and subsequently leading to cataract formation. [35] Variants in the CRYBA1 gene may lead to abnormalities in protein structure, preventing proper folding and assembly and thereby impacting the normal development and transparency of the lens. In addition to hereditary cataracts, CRYBA1 variants may also be associated with other ocular abnormalities such as corneal lesions and retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum stress (ERS) and unfolded protein response (UPR) are induced when the body is exposed to adverse external stimuli like ROS, which has been established that can induce different cell death modes, including autophagy, apoptosis [ 35 ]. A study showed that prolonged activation of the unfolded protein reaction (UPR) pathway and severe stress response can cause proteotoxic and endoplasmic reticulum stress (ERS), which induced cell death in CRYAA-Y118D mutant mice [ 36 ]. Autophagy is a fundamental cellular requirement for achieving the mature structure, homeostasis, and transparency of the lens [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HSPB4 R54H and R54C substitutions have been also detected in mice strains showing recessive congenital cataract (Chang et al, 1996;Chang et al, 1999;Xia et al, 2006). Another mutation, the HSPB4 Y118D substitution, has been obtained in two mouse models (Xia et al, 2006;Jia et al, 2021). Both HSPB4 Y118D mouse models recapitulate the phenotype and the biochemical and functional observations reported, which are the increased protein insolubility and UPR pathway activation in response to ER stress (Xia et al, 2006;Li et al, 2017;Jia et al, 2021).…”
Section: Hspb4 and Hspb5mentioning
confidence: 99%
“…Another mutation, the HSPB4 Y118D substitution, has been obtained in two mouse models (Xia et al, 2006;Jia et al, 2021). Both HSPB4 Y118D mouse models recapitulate the phenotype and the biochemical and functional observations reported, which are the increased protein insolubility and UPR pathway activation in response to ER stress (Xia et al, 2006;Li et al, 2017;Jia et al, 2021). Mutations causing substantial modification of the CTD include the HSPB4 Q147Rfs*48 frameshift mutation or point mutations at the stop codon (Javadiyan et al, 2017;Marakhonov et al, 2020).…”
Section: Hspb4 and Hspb5mentioning
confidence: 99%